Report from the scientific conference entitled: Saving the economy: reconstruction, stabilization and creation of economic development paths in the 19th and 21st centuries [Na ratunek gospodarce: odbudowa, stabilizacja i kreowanie ścieżek rozwoju gospodar - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2023)
In 2021, the Polish Association of Economic History (PTHG) prepared and submitted to the 21st General Congress of Polish Historians - Białystok 2024, a panel entitled “Saving the economy: reconstruction, stabilization and creating paths for the development of the Polish economy in the 19th and 20th centuries”, which was accepted by the congress organizers. The main goal of the research undertaken is to analyze systemic actions to overcome crises in the 19th and 20th centuries, in particular the activity of the state and public institutions “helping the economy”, the tools used and their effectiveness and long-term consequences. The events of the last three years, especially the Covid 19 pandemic, the War in Ukraine, and the energy crisis, have put the world economy once again on the threshold of a global crisis. In this context, scientific reflection on the tools and mechanisms of “saving the economy” and “creating development paths” may have not only a cognitive, but also a practical dimension.